Effect of Pu-erh tea pomace on the composition and diversity of cecum microflora in Chahua chicken No. 2 - Huang, Ying; He, Yongjiang; Peng, Zeqin; Hu, Hong; Yang, Minghua; Pan, Hongbin; Zhao, Sumei; Li, Yongneng (Frontiers in Veterinary Science, 2023)
Pu-erh tea pomace (PTP), a solid substance after extracting functional substances or steeping tea, is rich in crude protein, and crude fiber, and could be used as considerable bioactive substances in animal production. However, its application as poultry feed and its role in regulating the characteristics of gut microorganisms is unclear. The present study investigated the effects of PTP on growth performance and gut microbes of chicken. A total of 144 Chahua chickens No. 2 were individually housed and divided into three groups which were fed diets containing 0% (CK), 1% PTP (T1), and 2% PTP (T2), respectively. The serum and cecum contents were collected after slaughter for analysis. The results indicated that growth performance and carcass traits were not affected by the PTP content. Serum total triglyceride (TG), total cholesterol (TC), and low-density lipoprotein cholesterol (LDL-C) levels in the T1 and T2 groups were significantly lower than in the CK group (P < 0.05). The gut microbiota α-diversity in the T2 group was significantly lower than in the CK group (P < 0.05). Based on partial least squares-discriminant analysis ( PLS-DA), we observed significant segregation in gut bacterial communities among the groups. At the phylum level, Bacteroidetes and Firmicutes were dominant in the cecum, occupying about 85% of the cecum flora. The relative abundance of Bacteroidetes tended to increase. At the genus level, the relative abundance of Bacteroides is the highest in the CK、T1 and T2 groups. The relative abundances of Bacteroides and Prevotellaceae_UCG-001 microorganisms in the T2 group were significantly higher than in the CK group (P < 0.05). However, the relative abundance of CHKCI001 microorganisms in the T2 group was significantly lower compared to the CK group (P < 0.05). TG content was significantly positively correlated with CHKCI001 relative abundance, and significantly negatively correlated with Prevotellaceae_UCG-001 relative abundance (P < 0.05). Moreover, the LDL-C content was significantly positively correlated with CHKCI001 relative abundance (P < 0.05). In conclusion, PTP could decrease the cholesterol levels in the blood by improving the composition of gut microbiota, which provides a reference for the application of PTP in the poultry industry.